Modulation of the effects of cyclophosphamide on the lymphoid system of mice by double-stranded RNA - Sůla, K; Nouza, K (Folia biologica, 1985)
The ds RNA, an inducer of interferon, displayed a marked modulatory action on damage induced in the lymphoid system of mice by a single injection of cyclophosphamide. Its action depended on the type of lymphoid tissue and on the time interval between injection of ds RNA and CY. The "unwanted" synergy between the action of ds RNA and CY was most pronounced in the thymus in which a further great decrease in weight and cellularity was observed at all time intervals. In the case of the spleen and lymph nodes, the undesirable synergy was manifest only when the ds RNA was injected prior to CY. Simultaneous injection of ds RNA and CY, or injection of ds RNA after CY, had beneficial effects on the weight and cellularity of lymphoid organs, possibly by accelerating the regeneration processes.
Keywords: Interferons; Lymphoid Tissue; lymfatický systém; Liver; Mice, Inbred A; lymfoidní tkáň; játra; Lymphatic System; cyklofosfamid; myši inbrední C57BL; dvouvláknová RNA; Lymph Nodes; Mice; RNA, Double-Stranded; interferony; slezina; Organ Size; velikost orgánu; zvířata; Cyclophosphamide; lymfatické uzliny; Thymus Gland; myši; myši inbrední A; thymus; Spleen; Mice, Inbred C57BL; Animals